2018
DOI: 10.5194/amt-2018-111
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Field evaluation of low-cost particulate matter sensors in high and low concentration environments

Abstract: Abstract. Low-cost particulate matter (PM) sensors are promising tools for supplementing existing air quality monitoring networks. However, the performance of the new generation of low-cost PM sensors under field conditions is not well understood. In this study, we characterized the performance capabilities of a new low-cost PM sensor model (Plantower model PMS3003) for measuring PM2.5 at 1 min, 1 h, 6 h, 12 h and 24 h integration times. We tested the PMS3003s in both low concentration suburban regions (Durham… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
79
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(89 citation statements)
references
References 22 publications
10
79
0
Order By: Relevance
“…Kuula et al (2019) showed that inter-unit variability decreased as concentrations increased. In the same study, a magnitude of 264% of nRMSE was calculated for the Shinyei PPD60PV at low concentrations (< 4 μg m −3 ), which supports indications that performance of low-cost sensors improves as the PM concentration increases, since low concentrations are usually close to the noise level Zheng et al 2018). Nevertheless, high concentrations could be considered potentially negative, as a higher amount of particles can cause saturation of the photodetector and lead to poor performance.…”
Section: Accuracy Of Rh Sensor Measurements Compared To Reference Valuessupporting
confidence: 65%
See 1 more Smart Citation
“…Kuula et al (2019) showed that inter-unit variability decreased as concentrations increased. In the same study, a magnitude of 264% of nRMSE was calculated for the Shinyei PPD60PV at low concentrations (< 4 μg m −3 ), which supports indications that performance of low-cost sensors improves as the PM concentration increases, since low concentrations are usually close to the noise level Zheng et al 2018). Nevertheless, high concentrations could be considered potentially negative, as a higher amount of particles can cause saturation of the photodetector and lead to poor performance.…”
Section: Accuracy Of Rh Sensor Measurements Compared To Reference Valuessupporting
confidence: 65%
“…Since most low-cost PM sensors calculate concentrations based on the principle of light scattering, environmental variables such as temperature and relative humidity (RH) may significantly bias their measurements. Research conducted to date suggests the performance of the sensors decreases in environments with RH ≥ 75%, mainly due to hygroscopic growth of the particles after condensation of water droplets (Zheng et al 2018;Jayaratne et al 2018;Crilley et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Holstius et al (2014) found a negligible effect of temperature or RH on measurements performed using low-cost sensors under ambient conditions. However, several studies that used old PMS units, such as PMS1003 that was used in PA-I or PMS3003 that was never used in any PA units, found that these sensors were affected by RH (Kelly et al, 2017;Jayaratne et al, 2018;Zheng et al, 2018). AQ-SPEC (2018) tested the PA-II unit in a laboratory setting under different temperature and RH conditions and found that most temperature and RH combinations had 380 a minimal effect on the PA-II's precision.…”
Section: Temperature and Rhmentioning
confidence: 99%
“…The sensor package used a light-scattering PM 2.5 sensor (Plantower PMS3003) that had previously been evaluated against researchgrade reference monitors over different seasons and in both low-and high-PM environments (including in urban India). 4 Sensor packages documented minute-averaged concentrations of PM 2.5 , and were powered by a small external battery pack ( Figure 1). The UAV itself detected the elevation from ground level and carried a high-resolution camera capable of capturing both still images and video.…”
Section: Project 1: Assessing Landfill Emissions Using a Commercial Umentioning
confidence: 99%